Intraocular pressure investigation during lumbar spine surgery in prone position - Lyzohub, Mykola (ScienceRise: Medical Science, 2017)
Aim: to estimate intraocular pressure changes at lumbar spine surgery in prone position at the general intravenous anesthesia and at the spinal anesthesia and to compare these data with healthy volunteers. Materials and methods. The research included 10 healthy volunteers and 40 patients ASA І-ІІ, who underwent planned surgical interventions on the lumbar spine in prone position. Patients of І group (n=20, men 7,women 13, mean age 47±14 years) underwent surgical interventions under conditions of the spinal anesthesia. Patients of ІІ group (n=20, men 8, women 12, mean age 44±12 years) underwent surgical interventions under conditions of the general intravenous anesthesia. Patients’ prone position was horizontal in both groups. The head turned at the angle 45° (the left eye lower than the right one). The intraocular pressure was estimated by Maklakov’s method by one researcher in the position on the spine before surgery and immediately after it. Healthy volunteers (n=10, menв 4, women 6, mean age 49±12 years) were examined in the position on the spine, after that they lied in the analogous prone position during 90 minutes and were examined immediately after turning on the spine. Research results: patients of both groups and healthy volunteers demonstrated the increase of the intraocular pressure after lying in prone position (р<0,001), moreover it was higher in the left eye (the lower one). In patients of 2 group (general anesthesia) IOP increase in the low eye was reliably (р=0,03) more than in patients of I group and healthy volunteers. Patients of I group didn’t demonstrated reliable changes compared with the group of healthy volunteers. Conclusions: at turning in prone position healthy volunteers and patients under anesthesia (spinal, general) demonstrate the intraocular pressure increase. IOP increases in patients under the general anesthesia were reliably higher in the lower eye, than in patients of the group of the spinal anesthesia and healthy volunteers